Factors Associated With Differences in the Initial Location of Structural Progression in Normal-Tension Glaucoma. Issue 3 (March 2022) - Lee, Sang Yeop; Yang, Heon; Lee, Kwanghyun; Seong, Gong Je; Kim, Chan Yun; Bae, Hyoung Won
Abstract : Précis: Different clinical factors are associated with the location of the first structural progression in glaucoma. Purpose: The aim was to investigate the underlying clinical parameters affecting the location of the initial structural progression of glaucoma in patients with normal-tension glaucoma (NTG). Methods: This retrospective study included 228 eyes of 228 patients with NTG. In total, 130 eyes of 130 patients demonstrated structural progression (as determined by event-based guided progression analysis using Cirrus HD-optical coherence tomography) in the peripapillary retinal nerve fiber layer (ppRNFL) or macular ganglion cell inner plexiform layer (mGCIPL). Depending on where the progression occurred first, it was defined as either ppRNFL first progression or mGCIPL first progression. Clinical parameters associated with each first progression were identified using logistic regression. Results: In total, 50 eyes showed ppRNFL first progression and 64 eyes showed mGCIPL first progression. ppRNFL first progression was significantly associated with female sex [odds ratio (OR)=5.705, P =0.015], lack of systemic hypertension (OR=0.199, P =0.014), disc hemorrhage (OR=4.188, P =0.029), higher mean intraocular pressure (OR=1.300, P =0.03), and lower pattern SD (OR=0.784, P =0.028). In contrast, male sex (OR=0.450, P =0.043), lower central corneal thickness (OR=0.987, P =0.032), higher intraocular pressure fluctuation (OR=1.753, P =0.047), lower systolic blood pressure fluctuation (OR=0.839, P =0.002), and higher diastolic blood pressure fluctuation (OR=1.208, P =0.015) were significantly associated with mGCIPL first progression. Conclusions: Different clinical factors were associated with the initial site of structural glaucoma progression in patients with NTG depending on its peripapillary or macular location, and these findings suggest possible differences in underlying mechanisms of glaucoma damage.